The Impact of the Trade War Between China and the U.S. on the Economy of Indonesia - Vincentius Christian Laksmana (Syntax Corporation Indonesia, 2024)
China-US Trade War is an International Trade situation where two of the most powerful economic country increasing their tariff for trading goods to each other. The War itself actually occur for a long time but not as escalated as of 2018 which was started by the US itself and its current President, Donald Trump. Many people concern that this war may affect the world economy development since both of the countries are being the source of trading for many countries. This paper will discuss about how The China-US Trade War can influence Indonesia Economics which will bring either opportunity or problem. Research in this paper discusses about Indonesian Economy ranging from exports, imports, exchange rates and FDI which may be affected by Trade War using Correlation Test as research methods.